Density duct formation in the wake of a travelling ionospheric disturbance: Murchison Widefield Array observations. Issue 2 (8th February 2016) - Loi, Shyeh Tjing; Cairns, Iver H.; Murphy, Tara; Erickson, Philip J.; Bell, Martin E.; Rowlinson, Antonia; Arora, Balwinder Singh; Morgan, John; Ekers, Ronald D.; Hurley‐Walker, Natasha; Kaplan, David L.
Abstract: Geomagnetically aligned density structures with a range of sizes exist in the near‐Earth plasma environment, including 10–100 km wide VLF/HF wave‐ducting structures. Their small diameters and modest density enhancements make them difficult to observe, and there is limited evidence for any of the several formation mechanisms proposed to date. We present a case study of an event on 26 August 2014 where a travelling ionospheric disturbance (TID) shortly precedes the formation of a complex collection of field‐aligned ducts, using data obtained by the Murchison Widefield Array (MWA) radio telescope. Their spatiotemporal proximity leads us to suggest a causal interpretation. Geomagnetic conditions were quiet at the time, and no obvious triggers were noted. Growth of the structures proceeds rapidly, within 0.5 h of the passage of the TID, attaining their peak prominence 1–2 h later and persisting for several more hours until observations ended at local dawn. Analyses of the next 2 days show field‐aligned structures to be preferentially detectable under quiet rather than active geomagnetic conditions. We used a raster scanning strategy facilitated by the speed of electronic beamforming to expand the quasi‐instantaneous field of view of the MWA by a factor of 3. These observations represent the broadest angular coverage of the ionosphere by a radio telescope to date. Key Points: Travelling ionospheric disturbance triggers formation of field‐aligned density ducts Pronounced asymmetries in TEC gradients between eastern and western walls of density ducts Electronic beamforming enhances coverage speed of MWA radio telescope